Long-term recurrence-free survival in a patient with stage IVB uterine carcinosarcoma - Yoon, Gun (Korean Society of Gynecologic Oncology and Colposcopy, 2011)
Uterine carcinosarcomas are rare and highly aggressive tumors with a poor prognosis. Due to early metastasis and disease progression, it is known to be far more aggressive than matched grade 3 endometroid endometrial carcinomas. Five-year survival for stage IV is reported to be 10% and overall survival for stage IVB is expected to be very poor. The authors report one case after experiencing long-term survival (over 5 years) for stage IVB carcinosarcoma of uterus. Total abdominal hysterectomy and bilateral salpingo-oophorectomy was performed to 56 year old patient for uterine myoma. On pathology report, uterine carcinosarcoma was diagnosed and image studies were performed. With the impression of stage IVB uterine carcinosarcoma, 6 cycles of chemotherapy (ifosfamide and cisplatin) was conducted as adjuvant. Up to recently (over 5 years), she maintains good performance scale without evidence of tumor recurrence or disease progression.